OPTIMIZATION OF REAL-TIME ACCOUNTING IN SHARIA COOPERATIVES THROUGH THE IMPLEMENTATION OF THE APPSHEET APPLICATION - Eti Suprihatin; Junaedi Abdillah; Anum Dahlia; Irsan Putra Herlandi; Hendi Kurnia Permana (Universitas La Tansa Mashiro, 2026)
Digital transformation has become a necessity for modernizing the economic sector—particularly for Sharia cooperatives, which face demands for real-time accountability and transparency. At the Al-Kautsar Sharia Producer Cooperative, reliance on a manual accounting system resulted in delayed reporting, risks of human error, and limited transparency for members. This situation created a critical gap between operational processes and the need for rapid, accurate accounting. This study implemented a mobile-based accounting information system using AppSheet low-code technology integrated with Google Sheets to optimize real-time financial management. A descriptive qualitative case study approach was employed, involving observation, interviews, system development, and implementation. The results demonstrate that the AppSheet system improved recording efficiency by 80%, significantly reduced the risk of data errors, and enabled members to independently access real-time financial information (such as savings and loan balances). This initiative optimizes the cooperative's human resources, allowing it to capitalize on market opportunities without incurring high costs. The study contributes theoretically to the development of a low-code implementation framework within the Sharia cooperative sector to suport real- time accounting.